Evaluación del selle apical de tres sistemas de obturación de conductos: In vitro - Ramírez M., Tatiana; Picado P., Mónica; Montero A., Mauricio; Zeledón M., Rodolfo (Odovtos - International Journal of Dental Sciences, 2011)
The tridimensional filling of the root canal system is a desired condition to enhance the root canal treatment prognosis. The purpose of this study is to evaluate the sealing ability of three commercial root canal sealing systems. Forty samples were obtained from extracted lower first molars and randomly assigned in 3 experimental groups of 10 and 2 control groups containing 5 samples each. The root filling systems used were Epiphany®, GuttaFlow® and Gutapercha + Sultan® (lateral condensation). Passive immersion in china ink was used after preparation and filling of the root canal was completed. The Gutapercha + Sultan® group showed the highest mean penetration (1.7mm) and the highest percentage of samples with leakage (100%), whereas GuttaFlow® group had the lowest, 0.5mm and 30% respectively. We also observed significant difference of mean leakage between these two groups (p<0.05). After using the root filling systems under the conditions utilized in this study, we conclude that GuttaFlow® provides a better apical seal than the other groups.